Accuracy of the revised Addenbrooke Cognitive Examination (ACE-R) and Mini-Mental (MMSE) in a Quilombola community with low education attainment: results of a cross-sectional study - de Deus Cabral Júnior, João; de Oliveira, Bruno Luciano Carneiro Alves; Simon, Sharon Sanz; Passinho, Jhule Silva; Cappi, Carolina; Bertola, Laiss; Alves, Candida Helena L.; Simões, Vanda M. F.; Alves, Gilberto Sousa (Frontiers in Dementia, 2026)
BackgroundIlliteracy may overestimate screening test interpretation for older adults with suspected cognitive decline. In rural areas of Brazil, the illiteracy rate and the lack of valid cognitive instruments may postpone the diagnosis of cognitive disorders.ObjectiveTo determine the diagnostic accuracy of the Addenbrooke’s Cognitive Examination (ACE-R) and Mini-Mental State Exam (MMSE) as well as the prevalence of mild cognitive impairment (MCI) for older adults with low education in a Quilombola community placed in Northeast Brazil, compared to cognitively healthy.Methods204 participants were collected from a sociodemographic and clinical evaluation and were subsequently the ACE-R and MMSE. Among them, 25 subjects presented MCI, and 179 were classified as cognitively healthy.ResultsThe prevalence of MCI was 12.3%; optimal accuracy yielded highest values for the comparison between controls and MCI for both ACE-R [Area Under the Curve (AUC) = 0.96] and MMSE (AUC = 0.96).ConclusionThese findings support establishing reliable cutoff scores for cognitive assessment of older adults with low educational attainment, living in rural areas.